A Study on the EFL Learners’ Ability in Taking TOEFL Listening Test - Febronia Lasi; Edmundus Bouk (Universitas Cokroaminoto Palopo, 2022)
The recent study aims at investigating how far the ESP learners’ ability and the strategies they employed in mastering the Listening Comprehensions skills of the TOEFL test. The descriptive research design focused on content analysis was applied to gather the data taken by 25 students as participants of the study. In order to see the learners’ ability in Listening Comprehension (LC) skills, the 50 questions of Listening Comprehension Test were given through the Pre-Test and Post-Test during one semester course from the Longman Introductory Course For The TOEFL Test (Green Book) by Debora Philips (2004). The observation and the test were the instruments in obtaining the data needed. The data was then analyzed based on the 3 (three) major skills in Listening Comprehension part A, B, and C covered 12 sub-skills or the strategies applied. The result of the ESP learners’ ability in Listening Comprehension (LC) was moderately revealed and they were in the level of ‘Low Intermediate’ level in general. However, there was still few students had not improved yet. Moreover, in Part B (skill 7 – 9) gained the highest scores percentage among two other skills, followed by skill 10 – 12 in Part C Long Talks. Meanwhile, Part A (skill 1 – 6) achieved the lowest scores’ percentage in implementing the strategies, specifically in the skill of 4, 2 and 1 (Passives, Negatives, and Restatements) in sequent. Thus, it is suggested that students need to do more exercises on TOEFL Listening Part A suggested strategies by Philips (2004). Moreover, with the advanced of technology, learners can improve their English Listening skills by accessing the free online TOEFL courses from experts in the internet besides doing more drillings on YouTube channels and Podcasts.